2014
DOI: 10.17219/acem/37263
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Low-Level Energy Laser Radiation in Basic and Clinical Research

Abstract: Laser radiation has specific attributes: monochromaticity, high coherence and polarization. These properties result in the extensive use of lasers in medicine. Laser devices can be assigned into three basic groups by means of their level of energy: high, medium and low energy. All of these types of radiation are used in medicine. However, the most commonly used, in basic science and clinical studies, is low-energy radiation. Molecular effects of low energy laser irradiation on cells are generally described as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The use of low‐level laser therapy (LLLT) as a therapeutic tool was first described almost 50 years ago . Since then LLLT has been proven to be a treatment that is effective and with few colateral effects compared to other therapies prescribed for inflammatory and traumatic disorders . However, even after decades of continuous research, the exact mechanisms of low energy laser radiation action on the human body is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of low‐level laser therapy (LLLT) as a therapeutic tool was first described almost 50 years ago . Since then LLLT has been proven to be a treatment that is effective and with few colateral effects compared to other therapies prescribed for inflammatory and traumatic disorders . However, even after decades of continuous research, the exact mechanisms of low energy laser radiation action on the human body is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These effects on intracellular signaling may lead to various biological effects, demonstrated both on experimental models and on clinical trials .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the beneficial effects of LLLT on bone repair in experimental models of DM 12,13 . However, many other controversial data have been reported in the literature concerning the modulatory effect of LLLT on bone healing in diabetic animals, likely as a result of the variety of threshold parameters for energy density and intensity, including the irradiation time and the irradiation mode, used in the experiments 14,15 . Therefore, the purpose of this study was to assess the effect of a protocol of low-level laser therapy using diode GaAlAs laser on the bone repair in alloxan-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…The use of low-level laser (photobiomodulation therapy) after surgery is a safe and effective treatment that allows a good healing process, reduces inflammation and guarantees analgesia. 21,22 There is also the possibility to apply a cooling system such as hydrogel to avoid erythema and pain caused by heat exposure. 23 Thus, to perform the laser frenectomy, the anesthetic technique does not differ from that performed for resection with a cold-scalpel, although the amount of anesthetic salt required is lower.…”
Section: Discussionmentioning
confidence: 99%